Determination of Mineral Constituents, Phytochemicals and Antioxidant Qualities of Cleome gynandra, Compared to Brassica oleracea and Beta vulgaris - Moyo, Mack; Amoo, Stephen O.; Aremu, Adeyemi O.; Gruz, Jiri; Šubrtová, Michaela; Jarošová, Monika; Tarkowski, Petr; Doležal, Karel (Frontiers in Chemistry, 2018)
The study compared mineral, chemical and antioxidant qualities of Cleome gynandra, a wild leafy vegetable, with two widely consumed commercial vegetables; Brassica oleracea and Beta vulgaris. Mineral nutrients were quantified with inductively coupled plasma mass spectrometry (ICP-MS), phenolic compounds using ultra-high performance liquid chromatography coupled to a mass spectrometer (UHPLC-MS) and β-carotene and vitamin C using high performance liquid chromatography with a photodiode array detector (HPLC-PDA). The antioxidant potential was evaluated using 2,2–diphenyl–1–picryl hydrazyl (DPPH) and oxygen radical absorbance capacity (ORAC). Cleome gynandra had highest concentrations of phosphorus, potassium, calcium, iron, zinc, ascorbic acid, total phenolics and flavonoids; whereas sodium, magnesium, manganese, copper and β-carotene were higher in Beta vulgaris. The significantly higher antioxidant activity (P ≤ 0.05) exhibited by Cleome gynandra in comparison to the two commercial vegetables may be due to its significantly high levels of vitamin C and phenolic acids. These findings on the mineral, chemical and antioxidant properties of Cleome gynandra provide compelling scientific evidence of its potential in adding diversity to our diet and contributing towards the daily nutritional requirements of millions of people for food and nutritional security.